A PRAGMATIC ANALYSIS OF HUMOR USED IN ENGLISH MEETING CLUB - JUVRIANTO CHRISSUNDAY JAKOB (State University of Medan, 2023)
Humor is kind of learning tactics which become someone’s style in doing certain methods or learning technique individually. The aim of this research is to found the types and the effects of humor in meeting club. The samples were the learners of Meeting club. The instrument of this research is Audio recording. Based on the result of this research, there are three types of humor appear in meeting club, likes Teasing, Banter and Joking and they are to create communicative teaching and learning, to activate learner in teaching and learning, to increase of the student's English ability especially speaking skill. Finally, it was strongly recommended and effectiveness for humor as an aid to learning and instruction, and trying to eliminate problem in learning English by considering the effects of using humor in Meeting club.